Analysis of weaving sections using drones - Sayno, Charles Yves M.
Weaving is one of the least understood aspects of traffic flow. The presence of weaving in a road section cause conflicts which reduces the capacity and performance of that given section. This study used the technology of drones to analyze weaving sections, specifically the University Ave.-Commonwealth Ave. merge junction Traffic flow parameters such as the volume, density, and speed were determined using the videos recorded by the drones. Analysis of the weaving section were done by plotting the parameters to determine the effects of weaving on each parameter. The behavior of the weaving vehicles were analyzed by measuring the distance and time it takes for a vehicle to reach the middle of each lane as it changes lanes to weave successfully. Comparison on the effects of weaving and the behavior of weaving vehicles during off-peak and peak hours were also conducted. Results showed that weaving has effects on the speed, density, and volume of the section and most of the parameters follow the theoretical plot. Results also showed that weaving vehicles takes longer distances but shorter time during off-peak hours compared to peak hours. The effects of peak hours were also significant on the volume, speed, and density of the weaving section.